Conscience radicale et contestation du serment au XVIIe siècle en Angleterre : le cas des quakers - Cyril Selzner (Etudes Epistémè)
The relation between oaths and conscience was taken for granted in the seventeenth century. Swearing involved conscience in its religious as well as in its moral capacity, since God was called to witness. Oath-taking was therefore liable to be attacked from a religious point of view, as soon as radical transformations of the traditional understanding of conscience were under way. Such was the case with the Quakers, rejecting all forms of swearing for conscientious reasons. This contribution analyses the motivations, arguments and strategies of seventeenth-century Quakers as well as their relations to the theological, political and social issues of the time. The case of the Quakers is all the more interesting that they gradually developed a set of legal strategies to come to terms with their predicament, achieving in the long run some measure of change in the law and the official practice of swearing itself.